Analysis of antioxidant, cytotoxic and mutagenic potential of Agave sisalana Perrine extracts using Vero cells, human lymphocytes and mice polychromatic erythrocytes - Araldi, Rodrigo Pinheiro; dos Santos, Maristela Oliveira [UNESP]; Barbon, Fabiane Faria [UNESP]; Manjerona, Bruna Aparecida [UNESP]; Meirelles, Bruno Rosa [UNESP]; de Oliva Neto, Pedro [UNESP]; da Silva, Pedro Ismael; dos Santos, Lucinéia [UNESP]; Camargo, Isabel Cristina Cherici [UNESP]; de Souza, Edislane Barreiros [UNESP] (Elsevier, 2018)
Brazilian Northeast is the world's largest producer of Agave sisalana Perrine for the supply of the sisal fiber. About 95% of plant biomass, which comprise the mucilage and sisal juice, is considered a waste residual is discarded in the soil. However, the sisal juice is rich in steroidal saponins, which exhibits different pharmacological properties. Despite this, natural products are not necessarily safe. Based on this, this study analyzed the antioxidant, cytotoxic and mutagenic potential of three extracts derived from acid hydrolysis (AHAS), dried precipitate (DPAS) and hexanic of A. sisalana (HAS). These analyses were performed by in vitro and in vivo methods, using Vero cells, human lymphocytes and mice. Results showed that AHAS 50 and 100 can be considered a useful antineoplastic candidate due to their antioxidant and cytotoxic activity, with no genotoxic/clastogenic potential in Vero cells and mice. Although the comet assay in human lymphocytes has showed that the AHAS 25, AHAS 50 and AHAS 100 can lead to DNA breaks, these extracts did not promote DNA damages in mice bone marrow. Considering the different mutagenic responses obtained with the different methods employed, this study suggest that the metabolizing pathways can produce by-products harmful to health. For this reason, it is mandatory to analyze the mutagenic potential by both in vitro and in vivo techniques, using cells derived from different species and origins.
Keywords: Agave sisalana; Comet assay; Histone γ-H2AX assay; Micronucleus test; Mutagenesis